Evaluation of the Short-term Effect of Pemafibrate on Liver Fibrosis Biomarkers Stratified by FIB-4 Index in Patients with Type 2 Diabetes Mellitus and Hypertriglyceridemia - Kitao, Takashi; Tanaka, Takumi; Kubori, Motohiro; Komoda, Yoshio; Mori, Yukiko; Ibata, Takeshi (Internal Medicine, 2025)
Aims This study aimed to investigate the short-term effects of pemafibrate (PEMA) on the Fibrosis-4 index (FIB-4) and Aspartate Aminotransferase to Platelet Ratio Index (APRI) across three subgroups stratified according to FIB-4 for assessing the risk of liver fibrosis in patients with type 2 diabetes (T2D) and hypertriglyceridemia. Methods A total of 114 patients were stratified into three subgroups based on their FIB-4 score at the initiation of PEMA, following the FIB-4 classification: Group 1 (G1) (FIB-4<1.30, n =46), Group 2 (G2) (FIB-4 1.30 to <2.67, n =56), and Group 3 (G3) (FIB-4 ≥2.67, n =12). We evaluated the changes in FIB-4 and APRI three months after the initiation of PEMA in each subgroup. Subsequently, we compared the changes (Δ) in FIB-4 and APRI scores across the three subgroups. Additionally, we investigated the baseline parameters and changes in these parameters correlated with ΔFIB-4. Results The FIB-4 index exhibited a significant increase in G1 (p =0.003) but decrease in G3 (p =0.041). The APRI showed a significant reduction in both G2 (p <0.001) and G3 (p =0.034). ΔFIB-4 in G3 was significantly greater than that observed in G1 (p <0.001) and G2 (p =0.026), whereas ΔAPRI in G3 was significantly higher than that in G1 (p =0.002). ΔFIB-4 was inversely correlated with baseline FIB-4 and positively correlated with Δγ-glutamyl transpeptidase. Conclusions The short-term effect of PEMA on liver fibrosis markers was more pronounced in patients with T2DM and hypertriglyceridemia who exhibited elevated baseline FIB-4 values.